Frontispiece: A Nonarchetypal 5, 6‐Dihydro‐2H‐pyrano[3, 2‐g]indolizine‐Based Solution‐Solid Dual Emissive AIEgen with Multicolor Tunability. Issue 19 (3rd April 2017) - Raghuvanshi, Ashutosh; Jha, Ajay Kumar; Sharma, Ashutosh; Umar, Shahida; Mishra, Shachi; Kant, Ruchir; Goel, Atul
Abstract : Through screening of a synthetic library a novel class of dihydropyrano[3, 2‐ g ]indolizine (DPI)‐based solution–solid dual compounds with aggregation‐induced emission characteristics (AIEgens) was discovered by A. Goel et al. and is reported in their Communication onpage 4527 ff. The AIEgens operate by a restriction of intramolecular vibration (RIV) mechanism. A range of multicolor (red, yellow, green, and blue) solid‐state luminogens was synthesized. Detailed analysis of the crystal structure of the DPIs revealed a well‐defined set of noncovalent interactions (CH⋅⋅⋅O and/or CH⋅⋅⋅N), which blocked the motion of C2 ‐flexure leading to RIV, thus promoting highly emissive behavior in the solid state.